Temperature regulation for hydrodistillation of essential oil extraction process from garcinia mangostana linn (GML) pericarp - Pei Chin, Tan (2014)
Garcinia Mangostana Linn (GML), commonly known as mangosteen is an emerging category of novel functional foods sometimes called “the queen of fruit”. It is presumed to have a combination of appealing subjective characteristics such as taste, visual qualities and fragrance, nutrient richness, antioxidant streangth and potential impact for lowering risk of human diseases. GML contains natural antioxidant constituents such as phenolic compounds, which have attracted a great deal of public and scientific interest due to their health-promoting effects as antioxidants. Eight hundreds (800) grams of GML pericarps were used as the raw material to produce essential oil through hydrodistillation. Temperature of distilled water was measured to study the relation between the temperature and the composition in the essential oil. HPLC analysis report shows that the significant amount component contained in GML pericarp is Ferulic Acid. The relation between the temperature and concentration of Ferulic Acid cannot be determined since the mercury thermometer cannot measure a slightly elevation of temperature precisely. Boiling-point elevation occurs due to solute dissolved in the water